The Lost Get-Back Boogie : A Novel - Burke, James Lee, 1936- (Book collections on Project MUSE., 2004)
Before The Lost Get-Back Boogie appeared to wide acclaim in 1986, James Lee Burke had been out of print in cloth for thirteen years and his fifth novel had received a record 111 rejection letters. ""LSU Press put me back in the game and turned my career around, "" Burke says. The novels and stories Burke had written during those years of rejection eventually became the stuff of the Dave Robicheaux series, which has earned him two Edgar Awards. Reviews of The Lost Get-Back Boogie now seem prescient. ""This is the book that Burke was born to write-and you're grateful he did, "" wrote syndicated rev.